Strategies to Prevent Readmissions to Hospital for COPD: A Systematic Review. (4th July 2021) - Sharpe, Isobel; Bowman, Meghan; Kim, Andrew; Srivastava, Siddhartha; Jalink, Matthew; Wijeratne, Don Thiwanka
Abstract: Patients with chronic obstructive pulmonary disease (COPD) experience high rates of hospital readmissions, placing substantial clinical and economic strain on the healthcare system. Therefore, it is essential to implement evidence-based strategies for preventing these readmissions. The primary objective of our systematic review was to identify and describe the domains of existing primary research on strategies aimed at reducing hospital readmissions among adult patients with COPD. We also aimed to identify existing gaps in the literature to facilitate future research efforts. A total of 843 studies were captured by the initial search and 96 were included in the final review (25 randomized controlled trials, 37 observational studies, and 34 non-randomized interventional studies). Of the included studies, 72% ( n = 69) were considered low risk of bias. The majority of included studies ( n = 76) evaluated patient-level readmission prevention strategies (medication and other treatments ( n = 25), multi-modal ( n = 19), follow-up ( n = 16), telehealth ( n = 8), education and coaching ( n = 8)). Fewer assessed broader system- ( n = 13) and policy-level ( n = 7) strategies. We observed a trend toward reduced all-cause readmissions with the use of medication and other treatments, as well as a trend toward reduced COPD-related readmissions with the use of multi-modal and broader scale system-level interventions. Notably, much of this evidence supported shorter-term (30-day) readmission outcomes, while little evidence was available for longer-term outcomes. These findings should be interpreted with caution, as considerable between-study heterogeneity was also identified. Overall, this review identified several evidence-based interventions for reducing readmissions among patients with COPD that should be targeted for future research. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.1955338 .